2016
DOI: 10.1182/blood.v128.22.105.105
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Toxicity after Therapy for Diffuse Large B Cell Lymphoma Occurs Early and Results in Decreased Overall Survival.

Abstract: Diffuse large B cell lymphoma (DLBCL) is the most frequent non-Hodgkin lymphoma, with increasing incidence in the elderly population. Anthracycline-containing chemo immunotherapy can achieve high response rates and improved survival, but can result in cardiovascular toxicity, which can negatively affect short and long term survival, particularly in older patients. We conducted a retrospective analysis to determine the incidence of cardiovascular events after DLBCL and the effect these complications have on out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The one-year and three-year cumulative incidences were 9.7% (95% CI 7.1-13.2) and 14.7% (95% CI 11.5-18.9), respectively. 10 In our study, we also identified risk factors associated with CVM. Older age at diagnosis was significantly associated with a higher risk of CVM.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…The one-year and three-year cumulative incidences were 9.7% (95% CI 7.1-13.2) and 14.7% (95% CI 11.5-18.9), respectively. 10 In our study, we also identified risk factors associated with CVM. Older age at diagnosis was significantly associated with a higher risk of CVM.…”
Section: Discussionmentioning
confidence: 89%
“…An increased risk of cardiovascular complications in DLBCL has been described in many studies. 10,12,14,15,22 Limat et al showed that an anthracycline-based chemotherapy regimen caused cardiotoxicity among 180 patients treated for aggressive NHL, with 5-year cumulative risks for experiencing cardiac events or developing HF (defined by declining left ventricular ejection fraction) of 19% and 10%, respectively. 16 In a recent retrospective study, 400 patients with DLBCL had an elevated rate of cardiovascular events after diagnosis (defined as new coronary artery disease requiring revascularization, congestive HF, or new cerebrovascular accidents).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations